I, the Citizen : Unraveling the Power of Citizen Engagement - Balasubramaniam, R.; Venkatachalia, M. N. (Ithaca, NY : Cornell University Press, 2017)
I, the Citizen is an attempt to understand citizen development and engagement. R. Balasubramaniam takes the reader through interpretations of development initiatives at the grassroots and what good governance means to ordinary people. He unravels the power of citizen engagement through his experiences of leading civil society campaigns against corruption and towards strengthening democratic participation of people. I, the Citizen also deals with the philosophical underpinnings of public policies, drawing from his on-the-ground experience as well as engagement with those in the higher echelons of policymaking and implementation. The last section of the book provides glimpses into milestones of a development movement, which Balu founded and led, milestones that are responsible for a continued faith in citizen engagement despite the hindering forces.
Frontmatter -- CONTENTS -- Acknowledgments -- Foreword -- Preface -- Understanding development -- Voices from the grassroots level -- Governance, democracy and citizenship -- Information indeed is power - people and their right to information -- Citizen engagement and the fight against corruption -- Citizen engagement towards making democracy work -- Perspectives on policy -- An unending movement -- Epilogue: Citizen Engagement - Exemplars and Realities -- Glossary
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jul 2019)
Keywords: Political participation -- India -- Tsundur; Asian Studies; Sociology & Social Science; POLITICAL SCIENCE / Civics & Citizenship